2003
DOI: 10.1074/jbc.m211966200
|View full text |Cite
|
Sign up to set email alerts
|

Tyrphostin A23 Inhibits Internalization of the Transferrin Receptor by Perturbing the Interaction between Tyrosine Motifs and the Medium Chain Subunit of the AP-2 Adaptor Complex

Abstract: Several intracellular membrane trafficking events are mediated by tyrosine-containing motifs within the cytosolic domains of integral membrane proteins. Many such motifs conform to the consensus YXX⌽, where ⌽ represents a bulky hydrophobic residue. This motif interacts with the medium chain ( ) subunits of adaptor complexes that link the cytosolic domains of integral membrane proteins to the clathrin coat involved in vesicle formation. The YXX⌽ motif is similar to motifs in which the tyrosine residue is phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 41 publications
(53 reference statements)
5
99
0
Order By: Relevance
“…Based on this result, and on the evidence that the localization of MP to endosomes is hampered upon treatment with the inhibitor of endocytosis tyrphostin A23, we conclude that CaMV MP traffics in the endocytic pathway. In animal systems, tyrphostin A23 interferes specifically with the m2 recognition of Tyr signals (Banbury et al, 2003). The evidence that tyrphostin A23 suppresses the internalization of MP and that this is dependent on functional YXXF cargo signals suggests strongly that interaction with the m-subunit of a plant AP-2 complex is required for the internalization of this protein, lending support to the hypothesis invoking a direct link between endocytosis and the clathrin machinery in plants.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Based on this result, and on the evidence that the localization of MP to endosomes is hampered upon treatment with the inhibitor of endocytosis tyrphostin A23, we conclude that CaMV MP traffics in the endocytic pathway. In animal systems, tyrphostin A23 interferes specifically with the m2 recognition of Tyr signals (Banbury et al, 2003). The evidence that tyrphostin A23 suppresses the internalization of MP and that this is dependent on functional YXXF cargo signals suggests strongly that interaction with the m-subunit of a plant AP-2 complex is required for the internalization of this protein, lending support to the hypothesis invoking a direct link between endocytosis and the clathrin machinery in plants.…”
Section: Discussionsupporting
confidence: 50%
“…Tyrphostin A23 inhibits endocytosis by interfering with the m2 recognition of Tyr signals (Banbury et al, 2003;Ortiz-Zapater et al, 2006;Dhonukshe et al, 2007). In transfected protoplasts, treatment with tyrphostin A23 led to the reorganization of GFP-MP distribution, which concentrated almost exclusively at the cell surface and no longer in foci ( Fig.…”
Section: Tyr-based Sorting Motifs Are Essential For Tubule Formation mentioning
confidence: 99%
“…S11 A and B). In addition, we found that treatment with tyrphostin (tyr) A23, a specific inhibitor of clathrin-dependent endocytosis (26), can reduce the internalization of AMT1;3 spots and resulted in AMT1;3-EGFP coalescing into larger particles with an increased spot size and fluorescence intensity both under N-sufficient conditions (Fig. 4 C, I, and J and Movie S4) and high-ammonium treatment ( mutant.…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, we now know that at least one of these broad-spectrum inhibitors (i.e. tyrphostin A43) can directly inhibit receptor internalization by binding to the AP-2 endocytic adaptor complex independently of its inhibition of enzyme activity [42].…”
Section: Discussionmentioning
confidence: 99%